Modelling and Robust Trajectory Following for Offshore Container Crane Systems - Raja Mohd Taufika, Raja Ismail; That, Nguyen D.; Ha, Q. P. (Elsevier Ltd, 2015)
In stevedoring operations, the ship-to-ship transfer of containers in open-sea is becoming an alternative way to avoid port congestion and subsequently can increase port efficiency. This process involves a large container ship or a barge, equipped with a crane, and a smaller vessel which transports containers between the ship and the harbour. However, the harsh open-sea conditions can produce exogenous disturbances to the crane system during the load transfer. Besides, the uncertainties and disturbances in the crane system may degrade the control performance. Hence, one of the requirements of offshore container cranes is to enhance robustness of the crane control system. This paper addresses the problem of robust sliding mode control for offshore container crane systems subject to bounded disturbances and uncertainties. The mathematical model of the control plant is first derived whereas the effects of ocean waves and strong winds are taken into account. Then, a robust sliding mode controller is proposed to track an optimal trajectory of the crane system during load transfer. Extensive simulation results are given to show that the proposed controller can significantly suppress the effects of disturbances from the vessel's wave- and wind-induced motion.